2021
DOI: 10.3390/ijerph18094708
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of the SARS-COV-2 (COVID-19) Pandemic in Spain

Abstract: Background: The COVID-19 pandemic has hit both the Spanish economy and the population’s health hard. The result is an unprecedented economic and social crisis due to uncertainty about the remedy and the socioeconomic effects on people’s lives. Methods: We performed a retrospective analysis of the macroeconomic impact of the COVID-19 pandemic in 2020 using key indicators of the Spanish economy for the 17 Autonomous Communities (ACs) of the country. National statistics were examined in the search for impacts or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Such skill sets can pave the way for a renovated working approach in different sectors in the Saudi Arabian economy. On the other hand, Pinilla et al (2021) showed that autonomous regions in Spain are most dependent on the service sector, especially tourism, as being the most negatively affected by Covit-19 shock and the associated confinement measures, revealing structural weaknesses in productive sectors in the Spanish economy. Bocchino et al (2021) argued that an unexpected and stressful factor such as COVID-19 may lead to feelings of vulnerability and helplessness, which affect personal health and lower productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such skill sets can pave the way for a renovated working approach in different sectors in the Saudi Arabian economy. On the other hand, Pinilla et al (2021) showed that autonomous regions in Spain are most dependent on the service sector, especially tourism, as being the most negatively affected by Covit-19 shock and the associated confinement measures, revealing structural weaknesses in productive sectors in the Spanish economy. Bocchino et al (2021) argued that an unexpected and stressful factor such as COVID-19 may lead to feelings of vulnerability and helplessness, which affect personal health and lower productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We use the qualifier “biopsychosocial capture” to capture the experiences of the COVID-19 pandemic. These experiences include the biological exposure to the COVID-19 infection and the social and psychological experiences of the COVID-19 attenuation policies, which include lockdown, social distancing, loneliness, financial loss, unemployment [8], secondary health effects (e.g., weight gain) [9], and crime [10]. Many of these biopsychosocial pandemic adversities may be risk factors for psychosis, for example, loneliness [11] and social defeat [12].…”
Section: Introductionmentioning
confidence: 99%
“…A causal impact analysis was conducted using the Causal Impact package [ 19 ] over R-studio Version 1.4.1717. This analysis employed a Bayesian structural time series (BSTM) model, which is a state-space model for time series data [ 20 , 21 , 22 , 23 , 24 ]. The BSTM used in this study modelled the behaviour of the linear predictor and set up prior distributions for unknown quantities in the model for the data before the interventions.…”
Section: Methodsmentioning
confidence: 99%